Hubungan Pengetahuan Dan Sikap Remaja Putri Tentang Personal Hygiene Dengan Kejadian Keputihan Di SMAN 10 Surabaya: The Relationship of Adolescent Women's Knowledge and Attitudes About Personal Hygiene with the Incidence of Vaginal Discharge at SMAN 10 Surabaya - Maharrani Agustin Lestari (Jurusan Kebidanan Politeknik Kesehatan Kemenkes Surabaya, 2024)
Reproductive health problems in adolescents need serious attention and handling from the Government because adolescents are the successor of the nation's generation. therefore young women are expected to understand personal hygiene and the adverse effects of unhealthy behavior in maintaining the cleanliness of reproductive organs in order to avoid vaginal discharge. The purpose of this study was to analyze the relationship between knowledge and attitude of adolescent girls about personal hygiene with the incidence of vaginal discharge at SMAN 10 Surabaya. This research method used Correlation Analytic design with Cross Sectional approach. The population is all students (146 students) SMAN 10 Surabaya. Sampling used Simple Random Sampling. Samples were taken as many as 106 female students of SMAN 10 Surabaya. Data analysis was collected using a questionnaire of knowledge and attitudes of adolescents about personal hygiene and the incidence of vaginal discharge. Then the data were analyzed using the Chi-Square (X2 ) Test with a significance level ≤ 0.05. The results showed that the majority of adolescents' knowledge about personal hygiene was good, the majority of adolescents' attitudes were positive, the majority of adolescent girls did not have vaginal discharge and there was a relationship between adolescents' knowledge and attitudes about personal hygiene with the incidence of vaginal discharge at SMAN 10 Surabaya with (p = 0.000). Discussion Future researchers should be able to look for factors that cause vaginal discharge in adolescents and provide the latest innovations in efforts to improve adolescent reproductive health, especially vaginal discharge. Keywords: Knowledge, Attitude, Personal hygiene, Vaginal discharge.